الحماية الجنائية للزوجة من خلال مستجدات قانون العقوبات 15-19 - العربي, مومن مسعود; محمد البشير, الاشهب (University of Eloued جامعة الوادي, 2019)
يعتبر العنف الزوجي من الظواهر الاجتماعية التي انتشرت انتشارا واسعا في المجتمع الجزائري، والذي يمثل تهديدا كبيرا على استمرار الحياة الزوجية والأسرية، وينقسم العنف الزوجي إلى أنواع كثيرة منها العنف الجسدي، والعنف اللفظي، والعنف الاقتصادي وغيرها، الأمر الذي دفع المشرع إلى تعزيز حماية أكبر للزوجة خاصة في التعديل الأخير لقانون العقوبات. Spousal violence is a widespread social phenomenon in Algerian society, which poses a major threat to the continuation of marital and family life. Marital violence is divided into many types including physical violence, verbal violence, economic violence, etc., which has prompted Algerian legislators to promote greater protection To the wife in particular in the recent amendment to the Penal Code.
مذكرة ماستر تخصص شريعة وقانون
Keywords: قانون العقوبات، الحماية الجنائية ، العنف، تشديد العقوبة; Penal Code، Criminal Protection، Violence، Severe punishment